(untitled) (Applied Biological Research, 2023)
The present study aimed to phenotypically screen the okra hybrids and their parents so as to identify tolerant or resistant genetic material against yellow vein mosaic disease (YVMD) and okra shoot and fruit borer (OSFB). The present study included a total of 55 single cross hybrids, 16 parents, and one hybrid check “OH-102” which were evaluated during monsoon 2019 at three locations (Navsari, Achhalia, and Vyara) in Gujarat (India) in RBD design. The number of plants and fruits affected in each genotype was counted at final harvest and percent incidence calculated for YVMD and SFB. Okra genotypes were screened to know their response on thebasis of plant and fruit damage severity scale. Among 72 genotypes (55 hybrids + 11 lines + 5 testers), none was free from YVMD and SFB incidence. Among the parents, ‘Arka Anamika’ and ‘Arka Abhay’, categorized as moderately resistant to YVMD and SFB at all test locations, were identified as the most promising donors for future breeding. Among 55 hybrids and check 22, 17, and 14 hybrids and check “OH-102” categorized as moderately resistant for YVMD, 15, 13, 9 hybrids for Okra Shoot Borer (OSB) and 13, 15, 16 hybrids for Okra Fruit Borer (OFB) and check “OH-102” categorized as fair resistance at Navsari, Achhalia and Vyara, respectively. The least YVMD and OSFB incidence in hybrids showed relatively high/ average yield performance for fruit yield per plant at all locations, so these can be used in the further future breeding program.